Investigación en psicoterapia - Villegas, Orlando (1991)
The article comprises a reflection on psychotherapy as an art and as science its definition and the ethical and methodological issues with regard to psychotherapy research, including the therapist's and patient's variables, process variables and design variables.A review of results from research on the therapeutic method, the patient, the therapist and time as independent variables, arriving to a series of conclusions.